2013
DOI: 10.1371/journal.pone.0052757
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Upregulated Genes under Cold Stress in Cold-Tolerant Chickpea Using the cDNA-AFLP Approach

Abstract: Low temperature injury is one of the most significant causes of crop damage worldwide. Cold acclimatization processes improve the freezing tolerance of plants. To identify genes of potential importance for acclimatzation to the cold and to elucidate the pathways that regulate this process, global transcriptome expression of the chickpea (Cicer arietinum L), a species of legume, was analyzed using the cDNA-AFLP technique. In total, we generated 4800 transcript-derived fragments (TDFs) using cDNA-AFLP in conjunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 37 publications
0
18
0
1
Order By: Relevance
“…Such detailed information can also be used to understand coordination among different regulatory pathways and may be exploited in the agricultural crops to develop appropriate strategies to manage the abiotic stresses under field conditions. In chickpea, global transcriptome expression using complementary DNA-amplified fragment length polymorphism (cDNA-AFLP), differential display, or microarray techniques have been used to identify genes of potential importance for acclimatization/tolerance to cold and elucidate pathways regulating this process (Mantri et al, 2007;Dinari et al, 2013;Sharma and Nayyar, 2014). Using microarrays, 210 differentially expressed genes under cold were identified (Mantri et al, 2007).…”
Section: Genomics and Transcriptomics In Elucidating Molecular Responmentioning
confidence: 99%
See 1 more Smart Citation
“…Such detailed information can also be used to understand coordination among different regulatory pathways and may be exploited in the agricultural crops to develop appropriate strategies to manage the abiotic stresses under field conditions. In chickpea, global transcriptome expression using complementary DNA-amplified fragment length polymorphism (cDNA-AFLP), differential display, or microarray techniques have been used to identify genes of potential importance for acclimatization/tolerance to cold and elucidate pathways regulating this process (Mantri et al, 2007;Dinari et al, 2013;Sharma and Nayyar, 2014). Using microarrays, 210 differentially expressed genes under cold were identified (Mantri et al, 2007).…”
Section: Genomics and Transcriptomics In Elucidating Molecular Responmentioning
confidence: 99%
“…Using microarrays, 210 differentially expressed genes under cold were identified (Mantri et al, 2007). The cDNA-AFLP in association with 256 primer combinations revealed different transcriptderived fragments (TDFs) associated with cold in chickpea leaves (Dinari et al, 2013). Some of the TDFs showed a differential expression pattern and belonged to putative functions associated with transport, signal transduction pathways, metabolism, and transcription factors.…”
Section: Genomics and Transcriptomics In Elucidating Molecular Responmentioning
confidence: 99%
“…Members of the bHLH, WRKY, NAC, AP2-EREBP and MYB were found among the top differentially expressed TFs in stress condition [42]. In order to understand the effect of cold stress, AFLP-based transcript profiling (cDNA-AFLP) approach was used [67], which showed that in cold-tolerant chickpea, 102 transcript-derived fragments (TDFs) were differentially expressed during cold stress. Moreover, transcriptome analysis of cold-tolerant chickpea ICC 16349 using cDNA differential display (DDRT-PCR) resulted in identification of 127 ESTs as differentially expressed in anthers during cold stress conditions.…”
Section: Using Transcriptome Analysis For Study Of Stress Response Inmentioning
confidence: 99%
“…There has been a recent fl urry of publications demonstrating the isolation and characterization of abiotic stress-responsive genes and their potential transcriptional controllers from temperate legumes using several methods. This has included partial elucidation of the transcriptional responses and controls to drought, salinity and cold in chickpea using microarrays (Mantri et al 2007(Mantri et al , 2010b and most recently the more in-depth identifi cation of cold stress tolerance genes and transcription factors in chickpea using cDNA-AFLP (Dinari et al 2013 ). There exists tremendous opportunity to employ the high throughput and next-generation sequencing technologies to start to characterize the key functional roles of many genes and gene regulators that have been identifi ed.…”
Section: Regulation Of Abiotic Stress and Tolerancementioning
confidence: 99%